A comprehensive survey on formal concept analysis, its research trends and applications - Singh, Prem Kumar; Aswani Kumar, Cherukuri; Gani, Abdullah (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, FCA has received significant attention from research communities of various fields. Further, the theory of FCA is being extended into different frontiers and augmented with other knowledge representation frameworks. In this backdrop, this paper aims to provide an understanding of the necessary mathematical background for each extension of FCA like FCA with granular computing, a fuzzy setting, interval-valued, possibility theory, triadic, factor concepts and handling incomplete data.
Keywords: concept lattices; formal concept analysis; formal concept; formal context; Galois connection